Comprehensive characterization of neddylation related genes in cutaneous melanoma identified a novel prognostic signature for treatment outcomes, immune landscape - Min Zhang; Jian Liu; Fangxu Zhang; Qian Liang; Zhiqiang Guo (Discover Oncology)
Abstract Neddylation, as a post-translational modification, has garnered significant attention in various tumor types recently. Few studies have investigated the involvement of neddylation-related genes (NRGs) in cutaneous melanoma (CM). Our study aims to identify prognostic NRGs and investigate their potential roles in CM. The RNA-sequencing data and corresponding clinical data of CM patients were retrieved from The Cancer Genome Atlas (TCGA) database, while the expression profiles of 812 normal skin specimens were obtained from the Genotype-Tissue Expression (GTEx) database. The neddylation-related genes (NRGs) were extracted from the Molecular Signatures Database (MSigDB). We identified differentially expressed NRGs in CM and determined neddylation-related prognostic genes through univariate Cox regression analysis. We constructed a novel NRGs signature using LASSO-COX. The accuracy and utility of the NRGs signature were evaluated via a variety of statistical methods. Bioinformatics tools were employed to investigate the differential biological functions and signaling pathways among distinct risk groups. The expression levels of NRGs were analyzed through RT-qPCR experiments conducted in vitro. Finally, we identified an 8-NRGs signature in CM. Our prognostic model exhibited a high predictive capability for outcomes. The differences in the proportions of immune cells among subgroups were statistically significant. The in vitro experiments indicated significant differences in the expression of our NRGs. The 8-NRGs signature serves as a prognostic model for CM. Importantly, the novel biological prognostic model holds potential for personalized therapy in CM patients.